Tonsillar hypertrophy and prolapse in a child - is epiglottitis a predisposing factor for sudden unexpected death? - I. Nieuwoudt; P. Goussard; J. Verster; J. Dempers (BMC, 2020)
Abstract Background Tonsillitis, with associated tonsillar hypertrophy, is a common disease of childhood, yet it is rarely associated with sudden death due to airway obstruction. Lethal complications involving the inflamed tonsils include haemorrhage, retropharyngeal abscess and disseminated sepsis. Case presentation We report on a case of sudden and unexpected death in an 8-year-old female who was diagnosed with and treated for tonsillitis. The child was diagnosed with acute tonsillitis 2 days prior to her collapse and was placed on a course of oral antibiotics. There were no signs of upper or lower airway obstruction. She was found to be unresponsive by her caregiver and gasping for air in her bed in the early hours of the second morning after the start of treatment. Autopsy showed massive and symmetrically enlarged palatine tonsils. The tonsils filled the pharynx almost completely. The epiglottis and laryngeal mucosa at the base of the epiglottis in the vicinity of the aryepiglottic membrane and the superior aspect of the larynx displayed red-purple discoloration, with mucosal swelling and edema. Histological examination of the palatine tonsils revealed prominent lymphoid hyperplasia, but no evidence of acute inflammation. Conclusion Palatine tonsillar hypertrophy in infants is a common feature of both viral and bacterial tonsillitis and has been postulated as a possible risk factor for Sudden and Unexplained Death in Infancy (SUDI), based on the theory of mechanical impediment of breathing by narrowing of the upper airway. The rounded shape of the tonsils may facilitate some airflow past the enlarged structures and hence protect against asphyxial death when the enlarged tonsils fill the laryngo-pharynx. Epiglottal and proximal laryngeal edema may play a more significant role in asphyxial unexpected deaths in cases of tonsillitis with tonsillar hypertrophy than previously suspected. This focusses the importance of careful examination of the epiglottis and proximal laryngeal mucosa, as part of a thorough examination of the laryngo-pharynx in cases of sudden death associated with tonsillar hypertrophy.